Don't splash the sasquatch! - Redeker, Kent (Disney Hyperion Books, 2016)
Señor Sasquatch wants to relax beside Mr. Blobule's pool without getting wet, but he is thoroughly splashed by the other guests, who then pitch in to dry his "squizzlefied" fur.